“I do consider some of them to be racially white but they shall not be White”: Terrorist Manifestos and the Construction of White Masculinity - Hughey, Matthew (Journal of Critical Race Inquiry, 2025)
I investigate the public manifestos of Anders Brevik (2011); Patrick Crusius (2019); Payton Gendron (2022); Frazier Glenn Miller, Jr. (1999, 2002); Elliot Rodger (2014); Dylann Roof (2015), and; Brendon Tarrant (2019). I analyze these documents not as reflections of static identities or ideologies but as discursive mechanism that helps reproduce an ideal White masculinity as an ongoing accomplishment via (1) of defining the problem and assignment of blame in the essentialization of difference; (2) the proposal of prognostic strategies and tactics toward exercising dominance, and; (3) a call to arms through an appeal to emotional virtue. In so doing, I confront popular, media, and scholarly tendencies to psychologize and minimize the social dynamics within contemporary assemblages of White masculinity. I also show how some of the central themes within these manifestos are, despite being labeled as radical, extreme, and sporadic, resonate with widespread, banal, and largely accepted attitudes held by many White Americans today. I then turn to why these manifestos evidence the ongoing accomplishment of crisis white masculinity.